n vitro antioxidant activity and polyphenol estimation of methanolic extract of endangered medicinal tree species, Hildegardia populifolia (Roxb.) Schott & Endl. - Saradha .M; S. Paulsamy (International Journal of Phytomedicine, 2012)
Antioxidant property of methanolic leaf and stem bark extracts of the endangered medicinal tree species, Hildegardia populifolia was evaluated by studying the contents of total phenolics, tannins and flavonoids, free radical scavenging activity using 1,1-diphenyl-2-picryl hydrozyl (DPPH), hydroxyl radical scavenging activity, reducing power activity, ABTS·+ assay and metal chelating activity. The results of the study revealed that both the parts studied were found to have potent antioxidant activity against DPPH, hydroxyl and ABTS·+ radicals with the IC50 value of 92.86 and 309.83 for methanolic extracts of leaf and stem bark respectively for DPPH radicals and 820.30 (leaf) and 456.71 (stem bark) for hydroxyl radicals. Therefore methanolic extracts of both leaf and stem bark of H. populifolia can be considered as a new potential source of natural antioxidants for pharmaceutical industries.